God, design, and naturalism: Implications of methodological naturalism in science for science-religion relation - Bylica, Piotr; Sagan, Dariusz (Pensamiento. Revista de Investigación e Información Filosófica, 2015)
The aim of this paper is to analyze the implications flowing from adopting methodological naturalism in science, with special emphasis on the relation between science and religion. Methodological naturalism, denying supernatural and teleological explanations, influences the content of scientific theories, and in practice leads to vision of science as compatible with ontological naturalism and in opposition to theism. Ontological naturalism in turn justifies the acceptance of methodological naturalism as the best method to know the reality. If we accept realistic interpretation of scientific theories, then methodological naturalism conflicts science with religion. Theistic evolution does not seem to be a proper way to reconcile Darwinism and methodological naturalism with theism. Many of such propositions are boiled down to deism. Although evolution can be interpreted theistically, it is not the way in which majority of modern scientists and respectable scientific institutions understand it.